THE DISTRIBUTION OF PROFITS AND LOSSES, AS WELL AS MONETARY POLICY, IN ISLAMIC BANKS INDONESIA - Faizul Mubarok; Rusdianto (Universitas Airlangga, 2023)
Profit and loss distribution in Islamic banking financing is based on the principles of fairness and risk sharing between banks and customers. Islamic banking activities channel financing are an effort to move the economic sector. This study intends to examine the short- and long-term link between monetary policy and Mudharabah contract finance, as well as the shocks caused by changes in monetary policy and the contribution of each variable during shocks. The research makes use of a vector error correction model, which is applied to monthly data spanning the years 2004 to 2022. The sample population for the study is comprised of a number of Islamic commercial banks and business units. The findings of the research on interest rates have an effect on financing through Mudharabah contracts in both the short and long terms, but solely on inflation in the long term. However, the exchange rate does not affect the short or long term. Islamic banks must implement a portfolio of Mudharabah contracts and prepare reserve funds when a shock occurs. In Mudharabah contracts, financing Mudharabah is affected by interest rates, both short-term and long-term, but only long-term financing is affected by inflation. The most important change is the change in interest rates. If a change in a financial indicator causes a shock, Islamic banks need to set up reserve funds so they can handle it. To make Islamic banking more competitive, the government needs to keep taking it as seriously as setting interest rates.